A ambientalização curricular no curso de formação de professores de ciências e biologia na percepção dos licenciandos - Silva, Mariana Dias da (2014)
The development of a society based on sustainability and the need to work on environmental issues in a way that allows social change is increasingly gaining importance in the formation of society. To place the environmental theme in the curricula of higher education goes beyond considering it only as the teaching of the dynamic of the natural environment and environmental problems, but also includes the socio-political and cultural issues. In this sense, the environmental thematic in their pedagogical praxis involves the understanding of a education to citizenship, responsible, critical and participatory, which enables transformative decision-making, in order to build a sustainable, healthy and socially fair future. Given the above, and considering that the official documents governing education in the country propose the inclusion of environmental issues in the curriculum as an integrating theme, the present study aimed to verify the perception of undergraduate students on the environmentalization of the curriculum of a higher education institution. To achieve that purpose we performed collective reflective interviews with volunteer students. With the analysis of the results was noticed that although the studied higher education institution has been conducting studies and actions in the direction of the environmentalization of the curriculum, the undergraduates students of the institution not to perceive it more effectively in their activities and academic experience. The students point out that in the few moments where the theme is present it is only focused on the preservation of the environment and biodiversity, or on the presentation of the interrelationships between living beings and between living beings and their environment. The social, cultural, political, ethical and economic aspects are not discussed. It is believed that there is still a long way to go for effective implementation of environmental issues in the curriculum of the university, and this work, bringing the point of view of the student on the process contributes to the construction of the complex mosaic of the environmentalization of the curriculum as proposed by the ACES network.